Legal Politics In Realizing Social Justice In The Era Of Regional Autonomy - Ichsan Sjuhudi; Loso Judijanto; Resma Bintani Gustaliza (PT. Anagata Sembagi Education, 2024)
Legal politics plays a strategic role in realizing social justice in Indonesia, especially in the context of regional autonomy which aims to reduce social inequality. This research examines legal politics in Indonesia with a focus on the implementation of regional autonomy policies and their role in realizing social justice. Based on an analysis of Law No. 23 of 2014 on Regional Government, Law No. 33 of 2004 on Fiscal Balance, as well as data from various institutions, this research finds that although decentralization policies aim to strengthen equitable development, in practice, they often accommodate elite interests and exacerbate inequality. In addition, weak oversight of local financial management, low accountability, and unfairness in budget distribution are factors that exacerbate social inequality. Therefore, this study recommends strengthening the capacity of regions to plan development based on local needs as well as reforms in budget allocations that are more proactive for disadvantaged regions. Legal politics should be directed towards policies that support transparency, accountability and community empowerment to achieve the goal of equitable development. This research is expected to contribute to the development of more equitable and inclusive legal policies in the era of regional autonomy.